Alleviation of internal browning and fruit rot disease in ‘Pattavia’ pineapple using ethanolic shellac-modified coconut oil coating - Jiragittidoon, Phonmongkol; Sripong, Kanlaya; Boonyaritthongchai, Panida; Uthairatanakij, Apiradee; Jitareerat, Pongphen (Agriculture and Natural Resources, 2023)
Importance of the work: Internal browning (IB) and fruit rot disease are the main problems of harvested pineapple that limit its quality. Objective: To investigate the effect of ethanolic shellac-modified coconut oil (ES-MCO) coating against IB and fruit rot disease in ‘Pattavia’ pineapples. Materials & Methods: Fruits were coated with ES-MCO (consisting of 8% shellac and 2% MCO) and stored at 13°C and 95% relative humidity for 20 d. Uncoated fruits were used as the control. The IB, physiochemical qualities and rot disease were determined. Results: The ES-MCO treatment maintained fruit quality through a reduction in the respiration rate, resulting in a slower weight loss and color changes (peel and pulp). The browning index and browning scores of the coated fruits were lower than those of the control by 8.8% and 33.26%, respectively, while maintaining the total soluble solids/titratable acidity (TSS/TA) ratio and the ascorbic acid content. The ES-MCO treatment significantly reduced the polyphenol oxidase and peroxidase activity levels (browning enzymes), by 1.56–5.52 and 1.16–2.14 times, respectively, relative to the control. These results correlated with the reduction in IB and the increase in the total phenolic content. Compared to the control, the ES-MCO treatment slowed down the increase in the malondialdehyde content that is involved with the oxidative stress response, as well as suppressing rot disease. Main finding: Coating pineapple with ES-MCO alleviated IB and rot disease and delayed adverse changes in the physiochemical qualities caused by a reduction in the respiration rate.